2004
DOI: 10.3233/jad-2004-6310
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium, iron, zinc and copper influence the in vitro formation of amyloid fibrils of Aβ42 in a manner which may have consequences for metal chelation therapy in Alzheimer's disease

Abstract: Metals are found associated with β-pleated sheets of Aβ42 in vivo and may be involved in their formation. Metal chelation has been proposed as a therapy for Alzheimer's disease on the basis that it may safely dissolve precipitated Aβ peptides. We have followed fibrillisation of Aβ42 in the presence of an additional metal ion (Al(III), Fe(III), Zn(II), Cu(II)) over a period of 32 weeks and we have investigated the dissolution of these aged peptide aggregates in the presence of both desferrioxamine (DFO) and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
214
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(230 citation statements)
references
References 0 publications
13
214
1
2
Order By: Relevance
“…Then, as a function of parameters like solvent's pH and metal concentration, these two ions have shown different behaviors; in particular, under physiological conditions, the amyloid peptide has a higher propensity to bind zinc, whereas, under mildly acidic conditions, as in physiological acidosis following an inflammatory process, copper is preferentially bound; in other words, zinc can protect against copper toxicity, which is induced by acidosis [12,13]. In addition, studies with different concentrations of copper and zinc have shown that these metals prevent fibril formation of amyloid peptide by promoting the formation of no fibril aggregates [8,[14][15][16], like oligomeric aggregates that are more neurotoxic than the same fibrils [17][18][19][20][21][22][23][24]. Finally, other results obtained by structural studies, have shown that this peptide has two metal binding sites with higher and lower affinity: copper in high affinity site is coordinated in a planar configuration with three histidines and terminus or Tyr10 and this binding site is able to bind also a zinc ion [21,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Then, as a function of parameters like solvent's pH and metal concentration, these two ions have shown different behaviors; in particular, under physiological conditions, the amyloid peptide has a higher propensity to bind zinc, whereas, under mildly acidic conditions, as in physiological acidosis following an inflammatory process, copper is preferentially bound; in other words, zinc can protect against copper toxicity, which is induced by acidosis [12,13]. In addition, studies with different concentrations of copper and zinc have shown that these metals prevent fibril formation of amyloid peptide by promoting the formation of no fibril aggregates [8,[14][15][16], like oligomeric aggregates that are more neurotoxic than the same fibrils [17][18][19][20][21][22][23][24]. Finally, other results obtained by structural studies, have shown that this peptide has two metal binding sites with higher and lower affinity: copper in high affinity site is coordinated in a planar configuration with three histidines and terminus or Tyr10 and this binding site is able to bind also a zinc ion [21,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal ion chelators-One hypothesis that remains viable is that transition metal ions, including Al (III), Fe (III), Zn (II), and Cu (II), cause neurotoxicity and neurodegeneration (241)(242)(243), including in the earliest stages of AD (244). Excess accumulation of transition metal ions promotes oxidative stress, apoptosis, and aggregation and fibrillarization of hyper-phosphorylated tau (245) and AβPP-Aβ42 (243,246). Oxidative stress is mediated by the formation of hydroxyl radicals following interactions between iron and hydrogen peroxide.…”
Section: Radical Scavengers-epidemiological Studies Suggested That Lomentioning
confidence: 99%
“…67 Indeed, the prototype iron chelator, deferrioxamine (DFO), prevented the formation of ␤-pleated sheets of A␤ and dissolved preformed ␤-pleated sheets of plaque-like amyloid. 68 Also, ironinduced aggregation of hyperphosphorylated (tau), the major constituent of neurofibrillary tangles. 69 A direct link between iron metabolism and AD pathogenesis was provided recently by Rogers et al 70 who described the presence of an IRE in the 5' untranslated region (5'UTR) of the APP transcript.…”
Section: Selected Strategies In the Development Of Multifunctional Drmentioning
confidence: 99%